Legal and regulatory frameworks for waqf land development: the role and challenges of the Seberang Perai Tengah District and Land Office / Muhammad Adi Irfan Ramli - Ramli, Muhammad Adi Irfan (2025)
Waqf is a valuable asset in Malaysian society. This study aims to explore the Legal and Regulatory Frameworks for Waqf Land Development through the Role and Challenges of the Seberang Perai Tengah District and Land Office in assisting local authorities such as the Penang Islamic Religious Council (MAINPP) and the Penang Waqf Board in addressing issues such as legal obstacles and underutilized waqf land, particularly in Seberang Perai Tengah. This study aims to assess the current state of underutilized waqf land within the Seberang Perai Tengah district, to explore the role of the Seberang Perai Tengah District and Land Office in assisting in the development of waqf land, and to examine the legal and regulatory frameworks that impact the development of waqf land in Seberang Perai Tengah and propose recommendations for improvement. The study employs a qualitative approach to collect data through interviews with experts and practitioners directly involved in waqf land management, providing insights into the effectiveness of the district office's initiatives in revitalizing waqf land. Using semi-structured interviews, the key findings reveal the important role played by the district office in facilitating legal compliance, introducing beneficial policies in the National Land Code, Penang Land Rules 2021, and other regulatory instruments to assist in the registration and development of waqf land, such as waiving fees for waqf land registration. This can address pressing issues like affordable housing, food security, and community welfare through well-planned development projects. Additionally, the study proposes several recommendations to address legal challenges, including granting mosques greater autonomy in managing waqf land by formalizing management agreements with MAINPP and streamlining approval processes for mosque-led projects.